On Bounds of Eigenvalues of Complex Sturm-Liouville Boundary Value Problems - Wenwen Jian; Huaqing Sun (Abstract and Applied Analysis)
The paper is concerned with eigenvalues of complex Sturm-Liouville boundary value problems. Lower bounds on the real parts of all eigenvalues are given in terms of the coefficients of the corresponding equation and the bound on the imaginary part of each eigenvalue is obtained in terms of the coefficients of this equation and the real part of the eigenvalue.